STUDY ON THE DEVELOPMENT AND PERFORMANCE OF WATER DISTRIBUTION NETWORKS IN LANGARA URBAN AREA, SOUTHEAST SULAWESI - ILHAM KARI BUDI DARMAWAN; Bambang Bakri; Roslinda Ibrahim; Yasuhiro Arai; Mazlin Jumain (Universitas Trisakti, 2025)
Aims: This study was aimed to evaluates the development of the water distribution network in the IKK PDAM Lama of Konawe Kepulauan Regency- Southeast Sulawesi Province, Indonesia, particularly in West Wawonii Sub-district, which faces the challenge of increasing water demand due to population growth and urbanization. Methodology and results: The study utilized survey methods of water pressure, discharge, and physical condition of the network, as well as secondary data such as network maps and PDAM technical reports. Water demand projections were conducted based on the technical standards of the Minister of Public Works and Housing Regulation No.27/PRT/M/2016, with network hydraulics simulations using EPANET 2.2 software to analyze water pressure and flow under existing conditions and after network development. Conclusion, significance and impact study: Simulation results indicate that the water distribution network developed in 2025 fails to meet community demand, evidenced by negative pressure zones requiring network design revision. Initial optimization involved increasing the main pipe diameter to 150 mm and using Galvanized Iron Pipe (GIP) to reduce leakage, which satisfied demand until 2035 but fell short by 2040. Further optimization increased the main pipe diameter to 200 mm and the divider pipe to 160 mm, successfully meeting water demand until 2045. This study highlights the necessity of sustainable planning and continuous optimization in water distribution networks to maintain adequate service pressure and reliable clean water supply, especially in rapidly growing urban areas.